Controlled growth of zinc oxide nanorods by aqueous-solution method - Khusaimi, Z.; Amizam, S.; Mamat, M. H.; Sahdan, M. Z.; Ahmad, M. K.; Abdullah, N.; Rusop, M. (Taylor & Francis, 2010)
The controlled growth of zinc oxide nanorods in aqueoussolution is reported. Zinc oxide (ZnO) micro- and nano-rods were successfully prepared on gold-seeded Si substrates in aqueous solution containing 1:1 ratio of varying concentrations of zinc nitrate hexahydrate (Zn(NO3)2.6H2O) and hexamethylenetetramine (HMTA) (C6H12N4). The ZnO rods were characterized by scanning electron microscopy, X-ray diffraction and photoluminescence (PL) spectroscopy. A unique evolution of size and growth orientation is directly affected by the change in concentration of Zn2+ solution. The mechanism of growth governed by HMTA and chemical equations are suggested.